An Economic History of the Ancient World from the Palaeolithic Age to the Migrations of the Germanic, Slav, and Arab Nations. I - Heichelheim, F. M. (1958)
Hunters and Food-Gatherers of the Palaeolithic Age — Peasant Civilisation from the Mesolithic and Neolithic to the Iron Ages — Town Civilisation of the Ancient Oriental Copper and Bronze Ages from India to Crete — Archaic Mediterranean Iron Ages Civilisation.